Potential Antitubercular Agents, Part II: 4-Thiazolidione Derivatives - Solankee, Anjani; Kapadia, Kishor (Asian Journal of Chemistry, 2010)
4-Thiazolidinones have been synthesised by the condensation of thiourea with 2-bromo-adipic acid using ethanol in presence of pyridine as catalyst. The compounds have been screened for antitubercular activity using H37RV strain of bacteria. Their spectral studies are also included.